2011
DOI: 10.12659/msm.882130
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of walking-based outcome measures after multiple sclerosis relapses following steroid pulses

Abstract: SummaryBackgroundThe aim of this study was to examine the impact of intravenous methylprednisolone therapy (IVMP) on the recovery of walking ability in patients experiencing multiple sclerosis (MS) relapses, to compare the responsiveness of walking-based measures, and to estimate the impact of different walking-based measures responsiveness on clinical trials.Material/MethodsThe study included 49 consecutive patients with relapsing-remitting MS who received Solu-Medrol 1000 mg/day over 3 days for relapse with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
3
7
1
Order By: Relevance
“…We found low responsiveness of the T25FW, which is comparable to a prior study, which reported that the T25FW had a standardized response mean (SRM) of 0.55 and an effect size of 0.27 following intravenous methylprednisolone therapy for acute relapse in 49 people with MS (EDSS 1.0-6.0) 30. The same study reported that the MSWS-12 was highly responsive (SRM = 1.05, effect size = 1.02), whereas we found the MSWS-12 to be only moderately responsive 30. It is possible that patient-perceived changes of the impact of MS on their walking after treatment with methylprednisolone for an acute relapse were perceived as larger on the MSWS-12 than those elicited by our physical therapy intervention in people with stable disease.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found low responsiveness of the T25FW, which is comparable to a prior study, which reported that the T25FW had a standardized response mean (SRM) of 0.55 and an effect size of 0.27 following intravenous methylprednisolone therapy for acute relapse in 49 people with MS (EDSS 1.0-6.0) 30. The same study reported that the MSWS-12 was highly responsive (SRM = 1.05, effect size = 1.02), whereas we found the MSWS-12 to be only moderately responsive 30. It is possible that patient-perceived changes of the impact of MS on their walking after treatment with methylprednisolone for an acute relapse were perceived as larger on the MSWS-12 than those elicited by our physical therapy intervention in people with stable disease.…”
Section: Discussionsupporting
confidence: 82%
“…We also chose to evaluate responsiveness in the T25FW and the MSWS-12, as these are highly recommended outcomes for MS rehabilitation 6. We found low responsiveness of the T25FW, which is comparable to a prior study, which reported that the T25FW had a standardized response mean (SRM) of 0.55 and an effect size of 0.27 following intravenous methylprednisolone therapy for acute relapse in 49 people with MS (EDSS 1.0-6.0) 30. The same study reported that the MSWS-12 was highly responsive (SRM = 1.05, effect size = 1.02), whereas we found the MSWS-12 to be only moderately responsive 30.…”
Section: Discussionsupporting
confidence: 64%
“…( ) and Jensen et al ( ) both showed a larger change in walking time between before and after treatment using the SSST than the T25FW. Filipovic Grcic et al ( ) also showed a larger relative efficiency of the SSST than the T25FW, and the difference between the two was of similar size as in our study.…”
Section: Discussionmentioning
confidence: 90%
“…This would support the idea that such MCID values for steps/day are attainable in clinical research involving persons with MS who take part in a physical activity intervention, and perhaps other therapeutic interventions. Importantly, we are aware of one study that reported a change of ∼600 steps/day one month after treatment for a relapse using intravenous methylprednisolone therapy in 49 consecutive patients with RRMS [20].…”
Section: Discussionmentioning
confidence: 99%